CHRONOTOPE IN RUSSSIAN LITERATURE - Karimova Nigora Maratovna; Abdullaeva Tutiyo (Scientific Impulse, 2024)
Russian literature is rich with examples of the chronotope, a concept introduced by Mikhail Bakhtin. The chronotope refers to the intrinsic connectedness of temporal and spatial relationships that are artistically expressed in literature. In Russian literature, the chronotope is used to depict the unique cultural and historical context of different narratives. From the urban landscapes of Dostoevsky's St. Petersburg to the provincial settings of Tolstoy's works, the Russian literary tradition has beautifully captured the interplay between time and space. Furthermore, the chronotope has been instrumental in shaping the distinct narrative styles and thematic concerns found in Russian literature